2017
DOI: 10.1159/000475298
|View full text |Cite
|
Sign up to set email alerts
|

Pam3CSK4 Induces MMP-9 Expression in Human Monocytic THP-1 Cells

Abstract: Background: Matrix metalloproteinase (MMP)-9 is known to degrade the extracellular matrix and increased MMP-9 levels are related with the pathogenesis of many inflammatory conditions including obesity. Pam3CSK4 is a synthetic triacylated lipopeptide (LP) which is a potent activator of immune cells and induces cytokine production. However, it is unclear whether Pam3CSK4 is able to induce MMP-9 expression in monocytic cells. We, therefore, determined MMP-9 production by Pam3CSK4-treated THP-1 cells and also inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
5
23
0
Order By: Relevance
“…ERK 1/2and JNK can be activated by a variety of stimuli in various types of cells [26]. Our findings are consistent with our previous studies showing that activation of MAPKs pathways, except MAPK p38, is important for the production of MMP-9 [10, 14]. We also identified that inhibition of NF-kB pathways significantly suppresses the production of CCL4.…”
Section: Discussionsupporting
confidence: 92%
“…ERK 1/2and JNK can be activated by a variety of stimuli in various types of cells [26]. Our findings are consistent with our previous studies showing that activation of MAPKs pathways, except MAPK p38, is important for the production of MMP-9 [10, 14]. We also identified that inhibition of NF-kB pathways significantly suppresses the production of CCL4.…”
Section: Discussionsupporting
confidence: 92%
“…Each reaction contained 50 ng cDNA that was amplified with Inventoried TaqMan Gene Expression Assay products (SMPD3: Assay ID:Hs00920354_m1; SMPD2:Assay ID: Hs00906924_g1; SMPD1:Assay ID: Hs03679346_g1; CD11c: Assay ID: Hs00174217_m1; GAPDH: Hs03929097_g1;). The threshold cycle (Ct) values were normalized to the house-keeping gene GAPDH, and the amounts of target mRNA relative to control were calculated with ΔΔCt-method 35,36 . Relative mRNA expression was expressed as fold expression over average of control gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…Each reaction contained 500 ng of cDNA that was amplified with Inventoried TaqMan Gene Expression Assay products (CSF2: Hs00929873; ACSL1: Hs00960561; GAPDH: Hs03929097_g1). The threshold cycle (Ct) values were normalized to the housekeeping gene GAPDH, and the amounts of target mRNA relative to control were calculated with the ΔΔCt method [ 25 , 26 ]. Relative mRNA expression was expressed as fold expression over average of control gene expression.…”
Section: Methodsmentioning
confidence: 99%
“…MDA-MB-231 cells were treated with LPS and incubated for 30 min with lysis buffer (10X Lysis Buffer, Cell Signaling, Danvers, MA, USA). The protein lysates were prepared and resolved by 12% SDS-PAGE, as described earlier [ 26 ]. Cellular proteins were transferred to an Immuno-Blot polyvinylidene difluoride (PVDF) membrane (Bio-Rad Laboratories, Hercules, CA, USA) by electroblotting.…”
Section: Methodsmentioning
confidence: 99%